2020
DOI: 10.1139/cjfas-2018-0500
|View full text |Cite
|
Sign up to set email alerts
|

Improving data-limited stock assessment with sporadic stock index information in stock reduction analysis

Abstract: As most exploited fisheries lack a coherent time series of biomass index, development of data-limited stock assessment methods such as stock reduction analysis (SRA), is critical for fishery stock assessment due to their modest data requirements for estimating stock status and overfishing catch limits. In this study, we propose that sporadic time series of biomass indices, if available, may be fully utilized to inform priors of recent relative biomass (BT/B1) for data-limited stocks. We evaluated the performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Accordingly, data-limited methods have tremendous potential to be used in estimating fishery status and setting scientific catch limits, such as total allowable catch, for commercial fisheries in China Seas. For example, Guan et al (2020) improved stock reduction analysis with sporadic stock index information which could be collected from historical and recent fisheryindependent surveys in China. Our study provides another way to apply and validate COMs for data-limited fisheries in China Seas and stock reduction analysis such as Catch-MSY and CMSY could provide MSY-based reference points which could be used to inform fisheries management.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, data-limited methods have tremendous potential to be used in estimating fishery status and setting scientific catch limits, such as total allowable catch, for commercial fisheries in China Seas. For example, Guan et al (2020) improved stock reduction analysis with sporadic stock index information which could be collected from historical and recent fisheryindependent surveys in China. Our study provides another way to apply and validate COMs for data-limited fisheries in China Seas and stock reduction analysis such as Catch-MSY and CMSY could provide MSY-based reference points which could be used to inform fisheries management.…”
Section: Discussionmentioning
confidence: 99%
“…RLSADB summarized hundreds of formal stock assessments around the world and have been widely used to conduct empirical validation for COMs (Anderson et al, 2017;Free et al, 2020;Guan et al, 2020;Ovando et al, 2021b). In this study, only 23 fish stocks from RLSADB were found to satisfy our pre-defined criteria regarding catch trends and depletion levels.…”
Section: Discussionmentioning
confidence: 99%
“…Conducting fisheries‐independent surveys is still costly, but performance of management based on survey data may justify the cost by yielding more precise estimation of catch/effort limits, restoring stock biomass and resulting in higher yield (Dennis et al., 2015; Guan et al., 2019). Moreover, survey designs can be optimised with regard to specific management objectives to further improve the data quality and, subsequently, the performance of data‐limited survey‐based MPs (Xu, Zhang, et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…However, practical implementation of such strategies is hindered by heavy data demands, particularly catch‐at‐age data, which are widely unavailable (Su et al, 2020). In the meantime, there are numerous studies reporting the use of sporadic survey data to enhance the performance of data‐limited assessment methods in China (Chen et al., 2018; Guan, Chen, Boenish, Jin, & Shan, 2019; Sun et al., 2018; Zhang et al., 2018), indicating that survey‐based MPs have the potential to be integrated into China's fisheries management in the future and should be comprehensively evaluated for their performance, sensitivity and robustness.…”
Section: Introductionmentioning
confidence: 99%
“…Much of our understanding on data-poor species’ catch is based on landings data reported to the Food and Agriculture Organization of the United Nations (FAO)(Froese, Zeller, Kleisner, & Pauly, 2012). Data-poor species comprise >80% of global catch and almost two-thirds of species are overexploited (Costello et al, 2012; Guan, Chen, Boenish, Jin, & Shan, 2020). However, landings data are not consistent or reliable globally, particularly in countries with many landing sites and/or high levels of artisanal catch, particularly for sharks and their relatives (Khan et al, 2020; Okes & Sant, 2022; Ruano-Chamorro, Subida, & Fernández, 2017).…”
Section: Introductionmentioning
confidence: 99%